Meta Analisis: Pengaruh Persistensi Laba, Ukuran Perusahaan, Dan Leverage Terhadap Earning Responses Coefficient - Lafasya, Khalifa; Anggreani, Vemyta; Hendarto, Kris; Meiden, Carmel (Jurnal Riset Akuntansi dan Manajemen Malahayati (JRAMM), 2023)
ABSTRACTThe purpose of this research is to organize and determine the consistency of the findings of previous studies. The paper on the factors affecting the earnings response coefficient (earnings response coefficient) of earnings from 2012-2021 was the subject of our research. Methods of observation and literature study with the extension of meta-analysis were used to collect data. These studies included 10 published articles and 11 theses from Indonesian universities taken from the Publish or Perish, Eprints, and repository applications. The earnings response coefficient is significantly influenced by firm size, earnings persistence and leverage, according to the findings of this study. Because the average correlation is close to zero, the correlation between the independent variable and the dependent variable is very small. The positive correlation value indicates that the increase in the earnings response coefficient is directly proportional to the increase in the three variables examined in this study.